Optometric Management of a Third Nerve Palsy in a Prison Setting - Tousignant, Benoît (Canadian Journal of Optometry, 2017)
Third nerve palsy (TNP) is a neuro-ophthalmic condition that is likely to be encountered by optometrists in various clinical settings. It affects extraocular muscles and may impair eyelid and pupil functions to various degrees. Its aetiology in adults is often linked to compressive lesions of the central nervous system or to vascular ischemic causes from systemic disease such as diabetes and hypertension. This case report presents the management of a TNP in a multidisciplinary Canadian prison setting, where the patient population is often underserved. Current practices for neuroimaging cases of TNP in a conventional clinical setting are pre-sented. The challenges and advantages of management of TNP in a prison setting are discussed, highlighting the particularities of caring for the vul-nerable patient population in the prison setting.